1998
DOI: 10.2307/3434154
|View full text |Cite
|
Sign up to set email alerts
|

By-Products of a Former Phenol Manufacturing Site in a Small Lake Adjacent to a Superfund Site in the Aberjona Watershed

Abstract: Benzene, diphenyl sulfone (DPS), para-hydroxybiphenyl (PPP), ortho-hydroxybiphenyl (OPP), higher hydroxybiphenyls, and alkylated benzenes were found in a small lake receiving contaminated groundwater discharge from the Industri-Plex Superfund site (Woburn, MA) in the Aberjona watershed in eastern Massachusetts. All of these chemicals may derive from the former phenol manufacturing activities present at the Industri-Plex site during World War I.Concentrations up to 1660 pg/I benzene, 450 pgA DPS, 230 pgjA PPP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Today, it is mainly used as a monomer in the polymer industry and is a transformation product of phenols synthesis. It enters aquatic ecosystems through various sources and Wick et al affirmed that photochemical and chemical degradations are not significant in surficial water [25].…”
Section: Industrial Compoundsmentioning
confidence: 99%
“…Today, it is mainly used as a monomer in the polymer industry and is a transformation product of phenols synthesis. It enters aquatic ecosystems through various sources and Wick et al affirmed that photochemical and chemical degradations are not significant in surficial water [25].…”
Section: Industrial Compoundsmentioning
confidence: 99%
“…The origin of the plume is near the area of former distillation and storage facilities of crude benzene during World War I (28,29). We have previously reported that this benzene is presently discharging to the HBHA at about 30 kg/year (27). The lake is stratified year round with bottom waters always anoxic and sulfate-rich, while the epilimnetic waters are always oxic.…”
Section: Introductionmentioning
confidence: 99%
“…The HBHA receives benzene-contaminated groundwater input from an adjacent Superfund site (Industri-Plex). On Industri-Plex, large amounts of crude benzene (approximately 8000-21000 metric tons (27)) were converted to phenol during World War I. The groundwater just north of the lake contains a large benzene plume with peak concentrations near 60 µM (ca.…”
Section: Introductionmentioning
confidence: 99%